2009
DOI: 10.1001/jama.2009.1463
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Diseases and Risk of Hip Fracture

Abstract: Context Recent studies indicate common etiologies for cardiovascular disease (CVD) and osteoporotic fractures. Objectives To examine the relation between CVD and risk of hip fracture in twins and evaluate the relative importance of genetics and lifestyle factors in this association. Design, Setting, and Participants A cohort of all 31 936 Swedish twins born from 1914-1944 was followed up from the age of 50 years. The National Patient Registry identified twins with CVDs and fractures from 1964 through 2005. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
4
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(231 citation statements)
references
References 39 publications
8
209
4
10
Order By: Relevance
“…(7) In addition, the presence of coronary calcifications has been associated with a nonsignificant 8% lower lumbar spine BMD, (8) suggesting that there is an association between subclinical atherosclerosis and lower bone density in the elderly. Recently, it has been reported that cardiovascular disease (CVD), such as congestive heart failure and stroke, is associated with an increase in the risk of subsequent hip fracture, (9) providing further support for such a connection, even if the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…(7) In addition, the presence of coronary calcifications has been associated with a nonsignificant 8% lower lumbar spine BMD, (8) suggesting that there is an association between subclinical atherosclerosis and lower bone density in the elderly. Recently, it has been reported that cardiovascular disease (CVD), such as congestive heart failure and stroke, is associated with an increase in the risk of subsequent hip fracture, (9) providing further support for such a connection, even if the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…22,24 By contrast, such association was not found in a study based on selfreported data on hypertension obtained using self-administered questionnaires. 34 Sennerby et al 35 compared postmenopausal women having sustained a hip fracture with controls from the same region.…”
Section: Association Between the Prevalent Cardiovascular Pathology Amentioning
confidence: 75%
“…22 In a study that was a part of the Rochester Epidemiology Project, myocardial infarction was associated with higher risk of all types of osteoporotic fracture. 23 In a large Danish study carried out in about 500 000 individuals using the data from the National Health Service, a trial fibrillation was associated with higher risk of the fracture of hip, distal forearm or spine during the first 3 years after the incident.…”
Section: Association Between the Prevalent Cardiovascular Pathology Amentioning
confidence: 99%
“…In 2007, Sennerby et al showed that women with cardiovascular disease had a substantially increased risk of hip fracture, suggesting possible common pathologic pathways for osteoporotic fractures and cardiovascular diseases [32]. In addition, in a cohort of 31'936 Swedish twins born in followed up from the age of 50 years, the same authors reported that a diagnosis of cardiovascular disease was significantly associated with risk of subsequent hip fracture within the same individual and in his or her co-twin without index diagnosis [33]. In the present analysis, we report an increasing incidence of both major consecutive women and men aged 50 years and older and presenting to the emergency ward of participating hospitals with a fragility fracture [34], virtually all hip fractures, approximately half of proximal humerus fractures, one third of distal radius fractures, and one fourth of clinical spine fractures were hospitalized in Switzerland [3].…”
Section: Cost Of Hospitalizationsmentioning
confidence: 98%